Psychological skills, mental toughness, and competition anxiety among female handball players - Þórhildur Einarsdóttir 1995- (2019)
Research studies have shown that mental skills are essential for elite athletes to succeed. Psychological skills, mental toughness, and competition anxiety were observed among female handball players in the present study. The aim was to examine whether there was a difference depending on which level players played. Seventy-six players participated, divided into three groups; 18 had played for the national A team of Iceland, 24 were playing in the premier league (Olísdeild kvenna) in Iceland and 34 in the first league (Grill66 deild kvenna). Test of Performance Strategies (TOPS) was used to measure psychological skills, The Sport Mental Toughness Questionnaire (SMTQ) to measure mental toughness and The Sport Anxiety Scale – 2 (SAS-2) to measure competition anxiety. One-way ANOVA showed that there was no significant difference between groups in any sub-scale on the three questionnaires. Results are inconsistent with several studies on the topic, future research is though required for further assumptions. Keywords: psychological skills, mental toughness, competition anxiety Rannsóknir hafa sýnt að hugræn færni er mikilvæg fyrir íþróttamenn til að ná langt. Sálfræðileg færni, andleg þrautseigja og keppniskvíði voru rannsökuð hjá handboltakonum. Tilgangur rannsóknarinnar var að skoða hvort það væri munur á milli þeirra sem höfðu spilað fyrir A landsliðið og þeirra sem ekki höfðu spilað fyrir liðið. Sjötíu og sex leikmenn tóku þátt en þeim var skipt í þrjá hópa; 18 höfðu spilað fyrir A landsliðið, 24 spiluðu í Olísdeild kvenna og 24 í Grill66 deild kvenna. Test of performance strategies (TOPS) var notað til að mæla sálfræðilega færni, The sport mental toughness questionnaire (SMTQ) til að mæla andlega þrautseigju og The sport anxiety scale – 2 (SAS-2) til að mæla keppniskvíða. Einföld dreifigreining (e. one-way ANOVA) sýndi að það var enginn marktækur munur milli hópanna á neinum undirkvarða spurningalistanna þriggja. Niðurstöður eru ekki í samræmi við þó nokkrar rannsóknir á sviðinu en frekari rannsókna er þörf til ...